Reviewing Listening Arabic Skill using the Quizalize Application - Miatin Rachmawati; Ari Khairurrijal Fahmi; Alfred sirait (Izdihar : Journal of Arabic Language Teaching, Linguistics, and Literature, 2023)
This research was conducted to apply the Quizalize application to reviewing Arabic listening skills materials. This research uses a qualitative, descriptive case study approach. Data collection techniques include observation, interviews, documentation, and surveys. Based on existing data, there are three steps to conducting this media review. The first step is that students must download the Quizalize application at www.quizalize.com. The second step is to describe the competencies possessed by students. The third step is the results of the assessment of listening skills. The survey answered that Quizalize is able to train students to take tests carefully so as to increase their understanding of listening. especially Arabic language skills. Survey data stated that 72.1% of the reviews using Quizalize were very pleased, while 20.4% said that reviews using the Quizalize application had to prepare a large quota. However, 7.5% are less skilled due to a lack of understanding of Arabic vocabulary.